Large procyanidins prevent bile acid-induced oxidant production and membrane-initiated ERK1/2, p38, and Akt activation in Caco-2 cells - Da Silva, Mathieu (2012)
Procyanidins are oligomers of flavanol subunits present in large amounts in fruits and vegetables. Their consumption is associated with health benefits against colonic inflammation and colorectal cancer (CRC). Large procyanidins (with more than three subunits) are not absorbed by intestinal epithelial cells but could exert biological actions through their interactions with the cell membrane. This study investigated the capacity of hexameric procyanidins (Hex) to prevent oncogenic events initiated by deoxycholic acid (DCA), a secondary bile acid linked to the promotion of CRC. Hex interacted with Caco-2 cell membranes preferentially at the water–lipid interface. Hex (2.5–20 μM) inhibited DCA-triggered increase in cellular calcium, NADPH oxidase activation, and oxidant production. DCA promoted the activation of protein kinase B (Akt), of the mitogen-activated protein kinases ERK1/2 and p38, and of the downstream transcription factor AP-1. This activation was not triggered by calcium or oxidant increases. Hex caused a dose-dependent inhibition of DCA-mediated activation of all these signals. DCA also triggered alterations in the cell monolayer morphology and apoptotic cell death, events that were delayed by Hex. The capacity of large procyanidins to interact with the cell membrane and prevent those cell membrane-associated events can in part explain the beneficial effects of procyanidins on CRC.